Anthropometrics Identify Wasting in Patients Undergoing Surgery for Encapsulating Peritoneal Sclerosis. Issue 4 (July 2015) - Campbell, Rosalind; Augustine, Titus; Hurst, Helen; Pararajasingam, Ravi; van Dellen, David; Armstrong, Sheilagh; Bartley, Carol; Birtles, Linda; Summers, Angela
♦Introduction: Encapsulating peritoneal sclerosis (EPS) is a serious complication of peritoneal dialysis in which gastrointestinal (GI) symptoms reduce appetite and dietary intake. Adequate nutrition is important, especially if surgery is required. Although the incidence of EPS is low, the present report is able to detail preoperative nutrition status and treatment in a large cohort of patients from a national EPS referral center. ♦Methods: Of 51 patients admitted to this EPS specialist center hospital for their first peritonectomy in the study period, 50 had a preoperative dietetic assessment, and 49 underwent upper-arm anthropometry. ♦Results: Mean body mass index (BMI) was 20.6 kg/m 2 . Mean weight loss was 14% of body weight in the preceding 6 months, with 35 of 50 patients losing more than 10%. On anthropometry, 25 of 49 patients were below the 5th percentile for mid-arm circumference (MAC), 17 of 49 were below for triceps skinfold thickness (TSF), and 21 of 49 were below for mid-arm muscle circumference (MAMC). Mean handgrip strength (HGS) was 60% of normal, with 43 of 49 patients being below 85% of normal. Appetite was poor in 21 of 50 patients, and 37 of 50 had upper and 40 of 50 had lower GI symptoms. By subjective global assessment, 27 of 51 patients were graded as severely malnourished, and 5 of 51, as well-nourished. Mean serum albumin was 28 g/L and did not correlate with BMI, MAC, TSF, MAMC, or HGS. In most patients, C-reactive protein was elevated (mean: 111 mg/L). Preoperative parenteral nutrition was given to 46 of 51 patients for a mean of 21 days. ♦Discussion: Our findings demonstrate the poor nutrition status of patients admitted for EPS surgical intervention. Anthropometrics reveal depleted fat and lean body mass in EPS patients, which might be a result of anorexia and inflammation, and the reason that albumin was not an accurate marker of nutrition. Poor nutrition status is likely to negatively affect outcome in this patient group. ♦Conclusions: Early recognition of GI symptoms may herald a diagnosis of EPS. Optimization of preoperative nutrition status with intensive nutrition support is needed.